Total kinetic energy production of body segments is different between racing and training pace in elite Olympic rowers - Bechard, D. J.; Kedgley, A.; Nolte, V.; Jenkyn, T. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
The goal of competitive rowing is to cover a set distance as fast as possible (Baudouin and Hawkins, 2004). The role of the coach is to optimize each athlete`s technique and physiology through training to maximize their motive force and endurance. Training should therefore replicate the conditions of competition, at least in part, so that each athlete is prepared for the technical and physiological tasks demanded during the race. Different stroke rates are used in training sessions to achieve different goals. The majority of training is performed at `low` stroke rate (18-22 strokes per minute) to improve endurance and technique. A much smaller portion of training sessions are performed at `high` stroke rate (32-40 strokes per minute). This stroke rate is analogous to race conditions and is used for race familiarization and evaluation of athletic performance (Harrison et al., 2000). The purpose of this study was to calculate total kinetic energy (TKE) for each body segment of Olympic rowers during onwater training and to compare TKE, as a proxy for metabolic cost (Turvey et al., 1999), between low and high stroke rates.